2019
DOI: 10.1002/14651858.cd012711.pub2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surgical therapies for inflammatory bowel disease on female fertility

Abstract: Analysis 2.1. Comparison 2 Laparoscopic versus open surgery, Outcome 1 Infertiltiy at 12 Months..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 146 publications
1
32
0
Order By: Relevance
“…The median stool frequency after delivery was 6 (range, 4-10) times per day in the CS group and 6 (5)(6)(7)(8)(9)(10)(11)(12) in the VD group (p = 0.22). There were four patients with an increased stool frequency in the CS group and one in the VD group (p = 0.39).…”
Section: Pouch Function and Postpartum Complicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…The median stool frequency after delivery was 6 (range, 4-10) times per day in the CS group and 6 (5)(6)(7)(8)(9)(10)(11)(12) in the VD group (p = 0.22). There were four patients with an increased stool frequency in the CS group and one in the VD group (p = 0.39).…”
Section: Pouch Function and Postpartum Complicationsmentioning
confidence: 96%
“…Although the previous IPAA is stated as a relative indication for CS [10], the guidelines of the European Crohn's Colitis Organization stated that the appropriate delivery mode should be determined together with gastroenterologists, surgeons, and obstetricians [11]. In an observational study published in the Cochrane Library, the incidence of CS after IPAA significantly increased because of recommendations from colorectal surgeons, although not from obstetricians [12]. Presently, although several clinical situations need multidisciplinary care, no international clinical guidelines regarding the delivery mode for women after IPAA have been proposed by gastroenterological or obstetrical societies.…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that the laparoscopic approach results in improved fertility rates when compared to open surgery, likely due to reduced scarring of the fallopian tubes [59,60]. IBD surgery also appears to have a negative impact on pregnancy-related outcomes, including risks of miscarriage, need for assisted reproductive technology, delivery via caesarean section, and occurrences of stillbirth and preterm births, but there are conflicting results and poor-quality evidence [61]. Specifically, there is controversy on the need for cesarean section post-IPAA to prevent anal sphincter injury [56].…”
Section: The Impact Of Sexual Dysfunction On Fertilitymentioning
confidence: 99%
“…However, even if IBS itself does not seem to physically influence fertility, the medications which are commonly prescribed to treat this disorder could definitely affect one individual's ability to procreate. An unwanted surgical procedure or malnutrition resulting from IBS may provoke various sexual dysfunctions that may finally lead to infertility [17].…”
Section: Irritable Bowel Syndrome and Infertilitymentioning
confidence: 99%